A Numerical Study on the Oscillating Flow Induced by an Acoustic Field around Coal Particles. (5th September 2016) - Jiang, Genshan; Xu, Weilong; Liu, Yuechao; Wu, Yapan; Kong, Qian
Abstract : In order to investigate the acoustically driven oscillating flow around coal particles in the power plant boiler, the two-dimensional, unsteady mass and momentum conservation equations for laminar flow in spherical coordinates are developed numerically. The velocity field, axial pressure gradient, shear stress, and flow separation angle on the particle surface are carefully analyzed with different values of acoustic Reynolds number and Strouhal number. The minimum frequency required for flow separation is also investigated with different SPL (sound pressure level). The axial pressure gradient, shear stress, and separation angle on the surface are proportional to the magnitude of the oscillating flow velocity at low frequency ( 50 Hz). However, those physical quantities have different values at high frequency ( 5000 Hz), due to the combined effect of curvature and the flow acceleration.